Digital Transformation and Competitive Advantage of Small Firms: A Systematic Review of Capability Conversion - Aditya Fajar Fareza Repi; Asty Almaida (Penerbit Goodwood, 2026)
Purpose: This study consolidates fragmented evidence on how small and medium-sized enterprises convert digital transformation into competitive advantage through strategic capabilities, and develops an integrative conceptual framework.Research Methodology: The study applies a systematic literature review with thematic synthesis. Candidate records were identified through database and publisher-oriented searching, backward reference checking, and source tracing, then screened, appraised against a transparent rubric, and coded into descriptive and analytical themes. Every included record was independently verified for existence, authorship, year, outlet, and an active digital object identifier.Results: The synthesis identifies six themes: digital transformation as a capability-building process; digital capability and digital marketing capability; innovation capability as a value-conversion mechanism; market orientation, learning orientation, and strategic agility; competitive advantage and sustainable performance; and ecosystem, policy, and readiness constraints. The evidence indicates that digital adoption yields advantage only when it is embedded in firm-specific capabilities.Conclusions: Digital transformation becomes strategically valuable when it is converted into integrated capabilities that are aligned with market learning, translated by innovation, and deployed with agility.Limitations: The framework is conceptual and has not been tested empirically. Screening and appraisal were performed by a single coder, and the evidence base is cross-contextual rather than exclusive to emerging economies.Contributions: The study proposes the Digital Capability, Market Alignment, and Innovation framework with testable propositions, clarifying the pathway from digital adoption to competitive advantage and offering an agenda for research in Indonesia and other emerging economies.